2011
DOI: 10.5665/sleep.1130
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Wake and Phase Dependent Changes in Neurobehavioral Function under Forced Desynchrony

Abstract: The performance consequence of sleep restriction in our study was prominent during the biological night, even when the prior wake duration was short, and this performance consequence was in forms of waking state instability. This result is likely due to acute homeostatic sleep pressure remaining high despite the sleep episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 33 publications
(61 reference statements)
3
30
0
Order By: Relevance
“…Indeed, studies using constant routine or forced desynchrony paradigms have demonstrated the influence of both processes on variation in sleepiness and performance across the waking period (e.g. Dijk et al 1992; Mollicone et al 2008; Zhou et al 2011). Further research from us focuses on disentangling the effects of the circadian rhythm and homoeostatic sleep drive on attentional functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies using constant routine or forced desynchrony paradigms have demonstrated the influence of both processes on variation in sleepiness and performance across the waking period (e.g. Dijk et al 1992; Mollicone et al 2008; Zhou et al 2011). Further research from us focuses on disentangling the effects of the circadian rhythm and homoeostatic sleep drive on attentional functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recent forced desynchrony protocols, which serve to experimentally reveal the variance in neurobehavioral functions attributable primarily to endogenous circadian control and the variance attributable primarily to the sleep homeostatic drive, have revealed that circadian dynamics can expose large neurobehavioral vulnerability during chronic sleep restriction. 26,27 These studies demonstrated that sleep restriction induced decreased vigilant attention, as measured by the Psychomotor Vigilance Test (PVT), 25 most prominently during circadian night, even with short prior wake duration. Another study found that time of day modulated the effects of chronic sleep restriction, whereby the build-up rate of cumulative neurobehavioral deficits across days was largest at 0800 h and became progressively smaller across the hours of the day, especially between 1600 and 2000 h, indicating a late afternoon/early evening period of relatively protected alertness.…”
Section: Sleep–wake and Circadian Regulation: Two-process Modelmentioning
confidence: 99%
“…26,27 The interaction of the two systems is oppositional during diurnal wake periods (from approximately 0700 h until 2300 h), such that a relatively stable level of alertness and performance can be maintained throughout the day. 89,90 This explains why in many studies of alertness and performance, very little temporal variation is observed during the waking portion of a normal day, especially when there is no sleep deprivation 24 (Fig.…”
Section: Protocols To Assess Circadian Variation In Neurobehavioramentioning
confidence: 99%
“…Recent human CSR studies using forced desynchrony protocols (Cohen et al ., 2010; Zhou et al ., 2011) also reported cumulative deterioration in cognitive performance, which is evident especially when performance is measured during periods of forced wakefulness occurring lateduring the circadian ‘night’(Cohen et al .,2010). Cohen et al .…”
Section: Discussionmentioning
confidence: 99%